JPNIM and UENPS - Vassilios Fanos (Hygeia Press di Corridori Marinella, 2013)
The second issue of JPNIM comes with a surprise. JPNIM has become the official journal of the Union of European Neonatal Perinatal Societies (UENPS), formed by the societies of neonatal and perinatal studies in twenty-eight European countries. JPNIM focuses on interpreting the profound changes in the world of scientific research brought about by the possibility of acquiring enormous amounts of data ("big data") and the disposition to photograph the diagnostic, therapeutic and preventive organization of health programmes in Europe. It is not only the journal of what should be done, but of what is actually done in Europe to share, improve and harmonize knowledge in the different countries. Its international dimension is proven by the numerous contributions in this issue coming from Belgium, Bosnia and Herzegovina, Greece, Italy, Lithuania, Portugal, Sweden and Turkey. Its holistic vocation is tangible and recognizable in the passage from research to work in the field, with special emphasis on the Medical Humanities. The inclusion of the "Interview" column creates a strong bond between masters of consolidated reputation and brilliant young researchers to help make the passage from generation to generation effective and fruitful.